A pharmacoeconomic evaluation of the pharmacotherapeutic options for painful diabetic neuropathy. (24th March 2022) - Zhu, Jiejin; Li, Wanshu; Shi, Changcheng; Li, Qingyu
ABSTRACT: Introduction: Painful diabetic neuropathy (PDN) is a high incidence and severe complication of diabetes mellitus, significantly compromising patients' quality of life and causing tremendous economic burden. Considering drug costs becomes part of treatment decisions, with the growing choice of monotherapy or combination treatment strategies for PDN treatment. Areas covered: This systematic review aims to identify the cost-effectiveness of pharmacotherapies in PDN, summarize key findings, and assess the quality of studies to inform healthcare resource allocation decisions and future research. Economic evaluations were identified by searching PubMed, Web of Science, Scopus and health technology assessment (HTA) databases, as well as screening reference lists of previously identified studies. Relevant data was extracted, and the CHEERS checklist was used to assess the quality of the studies. Expert opinion: Collectively, the findings indicate that more pharmacoeconomics research is urgently needed to directly compare high-quality research for PDN combination medication/sequential treatment, and which is performed from a societal perspective. Simultaneously, to strengthen the reliability of the analysis, metrics such as adherence, incidence of adverse drug reactions, and pain levels utility value should be examined to verify the robustness of the basic results.